Hambatan komunikasi penyiaran radio Pro 2 FM Jakarta pada program morning live chat di masa covid-19 (Jurnal Kajian Media, 2021)
The COVID-19 pandemic has brought many changes to human life in terms of habits, psychology, communication, and people's social life. The process of communication and interaction between humans that is physically direct is also currently limited to avoid the transmission of COVID-19. This also has an effect on the radio sector, where initially all types of communication were direct, now they are not. This is certainly an obstacle for broadcasters in broadcasting communication. As happened in the Pro 2 FM Jakarta radio broadcasting communication on the Morning Live Chat program, where initially broadcast activities were carried out directly, but at this time it has become limited. This results in barriers to broadcast communication by broadcasters in carrying out the programs they run. This research will examine the broadcasting communication barriers that occur on Pro 2 FM Jakarta radio in the Morning Live Chat program, using qualitative research methods, constructivism paradigms, and ethical theory which results in that the obstacles that occur in broadcasting communication consist of several process barriers, physical barriers, semantic barriers, and psychosocial barriers. In this study, the data obtained through interviews and observations of broadcasters are expected to produce answers regarding the difficulties and communication barriers experienced by broadcasters during the COVID -19 pandemic in the broadcasting process. Keywords: Broadcasting Communications, Communication Barriers, Radio Pro 2 FM Jakarta, Morning Live Chat, COVID-19.